2011
DOI: 10.1182/blood-2010-06-290700
|View full text |Cite
|
Sign up to set email alerts
|

Irf8 regulates macrophage versus neutrophil fate during zebrafish primitive myelopoiesis

Abstract: IntroductionMyeloid cells or phagocytes are a subtype of leukocytes that play essential roles in the host defense, embryogenesis, organogenesis, and tissue regeneration. [1][2][3] In vertebrates, myeloid cells are classified into 2 major lineages: polymorphonuclear and mononuclear lineages, which acquire different morphologies during development and exert overlapping but distinctive biologic functions. Polymorphonuclear phagocytes consist of neutrophils, eosinophils, basophils, and mast cells. They are the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(182 citation statements)
references
References 48 publications
(66 reference statements)
10
170
1
Order By: Relevance
“…The consequential colonization of the wound by the local resident macrophages/neutrophils, distant/circulation-recruited neutrophils, and distant/circulation-derived macrophages is partially in agreement with the previous study in mice, which suggested that the local resident macrophages may facilitate the activation and recruitment of the distant/circulation-derived neutrophils and macrophages (44). However, contrary to this notion, our study showed that the activation and recruitment of both local resident and distant/circulation neutrophils are not affected in the irf8 morphants, in which resident macrophages and circulating monocytes are absent (28), indicating that the local resident macrophages are not essential for the activation and recruitment of distant/circulation-derived neutrophils. Further study is needed to clarify the role of the local resident macrophages.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The consequential colonization of the wound by the local resident macrophages/neutrophils, distant/circulation-recruited neutrophils, and distant/circulation-derived macrophages is partially in agreement with the previous study in mice, which suggested that the local resident macrophages may facilitate the activation and recruitment of the distant/circulation-derived neutrophils and macrophages (44). However, contrary to this notion, our study showed that the activation and recruitment of both local resident and distant/circulation neutrophils are not affected in the irf8 morphants, in which resident macrophages and circulating monocytes are absent (28), indicating that the local resident macrophages are not essential for the activation and recruitment of distant/circulation-derived neutrophils. Further study is needed to clarify the role of the local resident macrophages.…”
Section: Discussioncontrasting
confidence: 55%
“…To examine the co-staining of GFP and DsRed, embryos were first stained with goat anti-GFP and rabbit anti-DsRed antibody (1:250, 4°C, overnight) and subsequently visualized by Alexa Fluor 488 donkey anti-goat (1:400, 4°C, overnight) and Alexa Fluor 555 donkey anti-rabbit (1:400, 4°C, overnight). Similar methods were used for co-staining of GFP and Lcp protein and of GFP and phosphohistone 3 (pH3) (28). Anti-Lcp and anti-pH3 (Upstate) antibody was visualized by Alexa Fluor donkey anti-rabbit 555 (1:400, 4°C, overnight) (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory activation of early HSCs has been shown to be evolutionarily conserved [38], and a recent report by Hall et al [31] demonstrated that, in zebrafish, Gcsfr-NO signaling is required for the expansion of HSCs following infection. Among the irf family members, irf8 was shown to be required for myeloid differentiation into macrophages as opposed to neutrophils [39] and for the regulation of B-cell lineage specification and differentiation [40]. Here, we reveal that knocking down miR-142a-3p expression in zebrafish upregulated the expression of an irf family member, irf7, which might be responsible for the decreased HSC population in the miR-142a-3p morphants.…”
Section: Discussionmentioning
confidence: 67%